Social Media and Market Orientation in SMEs Performance: Competitive Advantage as Mediating Factor - Sinaga, Gilbert Johan Martin (KINERJA, 2025)
This research aims to examine the effect of social media and market orientation on SME performance mediated by competitive advantage in Riau Province. The novelty of this research, namely the use of the competitive advantage variable as an intervening variable, is still rarely studied in SMEs in Indonesia, and several previous studies have also shown a research gap. The population used in this research is SMEs in Riau Province. The sample in this research is 400 SMEs that were in accordance with predetermined criteria. The data used in this research are primary data with a questionnaire as the instrument. In addition, data collection in this research uses purposive sampling, where the number of respondents is 400. Data analysis uses Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with SmartPLS 4.0 software. The results obtained are (1) social media, market orientation, and competitive advantage have a significant effect on SME performance; (2) social media and market orientation have a significant effect on competitive advantage; (3) competitive advantage is significantly able to mediate the effect of social media on SME performance; (4) competitive advantage is not able to mediate the effect of market orientation on SME performance.